Cardiac factors as well as non-cardiac factors were associated with frailty in patients with heart failure with preserved ejection fraction. (25th November 2020) - Sunaga, A; Yamada, T; Yasumura, Y; Tamaki, S; Hayashi, T; Yano, M; Nakatani, D; Mizuno, H; Okada, K; Kitamura, T; Dohi, T; Kojima, T; et al.
Abstract: Background: Frailty is associated with malnutrition and poor prognosis in patients with heart failure with preserved ejection fraction (HFpEF). However, the cardiac factors associated with frailty have not been fully examined in patients with HFpEF. Purpose: The purpose of this study is to clarify the cardiac factors related to frailty in patients with HFpEF. Methods: Of the 756 patients who registered prospective, multicenter, observational study of patients with HFpEF (PURSUIT-HFpEF) registry, 481 cases with clinical frailty score (CFS) and prognosis after discharge were examined. Frailty was defined as CFS ≥5. Outcomes were composite endpoint of all-cause death and heart failure readmission, and all-cause mortality. We compared outcomes between patients without and with frailty, and sought to identify factors which were associated with increase in clinical frailty score by the correlation analysis and linear regression analysis. Results: Of 481 patients, 131 patients (27.2%) were frail. Male gender was less in patients with frailty than those without frailty (26.7% vs 73.3%, P<0.001). Frail patients had higher age (85.2±7.3 vs 78.7±9.4 years, P<0.001). During follow-up period of 396 [343, 697] days, composite endpoint (Kaplan-Meier event rate estimates, 77% vs. 60%; log-rank P<0.001), and all-cause mortality (Kaplan-Meier event rate estimates, 57% vs. 28%; log-rank P<0.001) was higher in patients with frailty than those without frailty. Multivariate Cox regression analysis revealed frailty was significantly and independently associated with mortality (HR=1.40, 95% CI=1.17–1.68, P<0.001). CFS was significantly correlated with age (r=0.401, P<0.001), sex (r=0.223, P<0.001), body mass index (r=−0.146, P=0.001), hemoglobin (r=−0.148, P=0.001), albumin (r=−0.222, P<0.001), left ventricular diastolic diameter (r=−0.184, P<0.001), interventricular septum thickness (r=−0.124, P=0.008), left ventricular mass (r=−0.217, P<0.001), tricuspid annular plane systolic excursion (r=−0.165, P=0.001), and tricuspid regurgitation pressure gradient (TRPG) (r=0.189, P<0.001). Multivariate linear regression analysis using these factors as covariates revealed age (standardized β: 0.337, P<0.001), sex (standardized β: 0.120, P=0.014), albumin (standardized β: −0.151, P=0.003) and TRPG (standardized β: 0.129, P=0.005) were significantly and independently associated with increase in clinical frailty score. Conclusion: Our results suggest that not only nutritional factors but also a cardiac factor were associated with frailty, and frailty was associated with mortality in patients with HFpEF. Improvement of hemodynamics in HFpEF patients as well as improvement of nutrition might contribute to alleviation of frail in HFpEF patients. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Roche Diagnostics K.K.; Fuji Film Toyama Chemical Co. Ltd.